Actin polymerization and leukocyte function - Howard, T H; Watts, R G (Current opinion in hematology, 1994)
The coordinated remodeling of the filamentous actin-based microfilamentous cytoskeleton via regulated polymerization and depolymerization of globular and filamentous actin is required for polymorphonuclear leukocyte motile functions including locomotion, shape change, phagocytosis, and adhesion. Significant new observations on the structure and function of distinct filamentous actin pools in polymorphonuclear leukocytes, the mechanisms of chemotactic peptide-mediated actin polymerization, the role of filamentous actin in polymorphonuclear shape change in suspension and on a surface, the identification and characterization of rare patients with polymorphonuclear motile defects and actin dysfunctions, and regulation of actin reorganizations by actin regulatory proteins, the phosphorylation or dephosphorylation states of proteins, and the second messengers--the phosphoinositides--were reported in the past year. These observations form the basis for an improved understanding of the cellular and molecular role of actin assembly in polymorphonuclear function and are the subject of this review.